Dual effect of Plasmodium -infected erythrocytes on dendritic cell maturation - Ocaña-Morgner Carlos; Galan-Rodriguez Cristina; Carapau Daniel; Bettiol Esther; Rodriguez Ana (Malaria Journal, 2010)
Abstract Background Infection with Plasmodium is the cause of malaria, a disease characterized by a high inflammatory response in the blood. Dendritic cells (DC) participate in both adaptive and innate immune responses, influencing the generation of inflammatory responses. DC can be activated through different receptors, which recognize specific molecules in microbes and induce the maturation of DC. Methods Using Plasmodium yoelii , a rodent malaria model, the effect of Plasmodium -infected erythrocytes on DC maturation and TLR responses have been analysed. Results It was found that intact erythrocytes infected with P. yoelii do not induce maturation of DC unless they are lysed, suggesting that accessibility of parasite inflammatory molecules to their receptors is a key issue in the activation of DC by P. yoelii . This activation is independent of MyD88. It was also observed that pre-incubation of DC with intact P. yoelii -infected erythrocytes inhibits the maturation response of DC to other TLR stimuli. The inhibition of maturation of DC is reversible, parasite-specific and increases with the stage of parasite development, with complete inhibition induced by schizonts (mature infected erythrocytes). Plasmodium yoelii -infected erythrocytes induce a broad inhibitory effect rendering DC non-responsive to ligands for TLR2, TLR3, TLR4, TLR5, TLR7 and TLR9. Conclusions Despite the presence of inflammatory molecules within Plasmodium -infected erythrocytes, which are probably responsible for DC maturation induced by lysates, intact Plasmodium -infected erythrocytes induce a general inhibition of TLR responsiveness in DC. The observed effect on DC could play an important role in the pathology and suboptimal immune response observed during the disease. These results help to explain why immune functions are altered during malaria, and provide a system for the identification of a parasite-derived broad inhibitor of TLR-mediated signaling pathways.